Predictors of Bone Mineral Density Reduction in Patients with Hodgkin’s Lymphoma Associated with Pathogenetic Therapy - Y. S. Kitaeva; E. A. Praskurnichiy (Архивъ внутренней медицины)
Hodgkin’s lymphoma is more common in the younger patient population. An increase in overall and recurrence-free survival increases the likelihood of developing post-cytostatic complications in the form of a decrease in bone mineral density and associated low-energy fractures.The aim of the work is to evaluate risk factors for bone mineral density decrease in patients with Hodgkin’s lymphoma after standard polychemotherapy and autologous hematopoietic stem cell transplantation.Material and Methods: The study included 118 people, of which 88 people were patients with Hodgkin’s lymphoma and 30 people were the control group. The study group of patients with Hodgkin’s lymphoma was divided into 2 groups: patients who received standard polychemotherapy and patients who received standard polychemotherapy and autologous hematopoietic stem cell transplantation. For all patients, measurements of bone mineral density were performed using the HologicDiscovery QDR scanner (USA) in the lumbar spine (L2–L4) and in the thigh region (total area of t he thigh and femoral neck). The minimum measurements of bone mineral density and T-scores in the hip and femoral neck were selected, and the Z-score was calculated for young patients.Results: According to the results of densitometry in both study groups, there was no decrease in bone mineral density below the age norm. In 13 patients (30 %) who received autologous hematopoietic stem cell transplantation, a decrease in T-score was found, which corresponds to osteopenia and osteoporosis. In the standard PCT group, a decrease in the T-criterion was observed in 6 patients (14 %): to stagnation — in 3 patients (7 %), to osteoporosis — in 3 patients (7 %). All patients with Hodgkin’s lymphoma included in the study received high doses of glucocorticosteroids. There was no correlation between the decrease in BMD, Z-criterion and the risk of low-energy fracture on the stage and variant of the disease.Conclusion: The high incidence of bone density reduction, taking into account a favorable prognosis for the life of patients with Hodgkin’s lymphoma, indicates the need to develop schemes for the prevention of osteoporosis and osteopenia.